The Impact of Early Marriage on Adolescent Development with Islamic Law - Muhammad Fadian Ilham; Didik Himmawan; Qusnul Khotimah; Alissyah Apriliani (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
The aim of this research is to inform and dedicate the meaning of marriage, early marriage, factors causing early marriage, the impact of early marriage and early marriage from an Islamic legal perspective. This research method is a qualitative research method with a qualitative library study approach, reference sources or libraries, namely the primary source is E-Books and the secondary sources are articles, journals and verses from the holy Koran. Marriage is a need and even a desire, but there will be challenges fighting lust if there is not enough readiness to marry legally or religiously. Early marriage, the term early marriage or young marriage is actually not known in the Big Indonesian Dictionary (KBBI ) but what is more popular is underage marriage, marriage at an age where a person has not yet reached adulthood, while the internal term for early marriage is known as (child marriage or early marriage) is a marriage that occurs in children under the age of 18, there are many impacts impacts that can be detrimental to us in the future, whether it is the impact on our own health, the child who will be born or family harmony.